Socially marginalized environments, unemployment and media - Oto Moravčík (DANUBE: Law, Economics and Social Issues Review, 2014)
In any society, regardless of its homogeneity and heterogeneity, there are minority groups, or those that require special attention and treatment because of their social and cultural characteristics, physical appearance, or because they have a lifestyle which differs from the dominant group and this causes them to be allocated the social status of minorities. The ongoing transformation of the economy since 1989 is now a major effect which continues to affect economic development. The planned economy and socialist market economy was replaced with the principles of free enterprise and the market mechanism. The market economy is closely tied to the labor market, which we view as the meeting point of labor supply with labor demand, resulting in labor costs - or wages. Position in the labor market is one of the most important factors through which an individual integrates into the social fabric. The aim of this scientific article is to describe the role of the media and outline its potential use in order to achieve changes in behavior and increase education levels in socially marginalized environments and resulting in greater social inclusion.
Keywords: 330; Ethnic Minorities; Unemployment; Community Center; the Roma Minority; the Media; Social Groups; Social Exclusion; Social Inclusion